Pro-poor intervention strategies in irrigated agriculture in Asia: poverty in irrigated agriculture: issues and options: China - Jinxia Wang; Jikun Huang; Zhigang Xu; Rozelle, Scott; Hussain, Intizar; Biltonen, Eric; Qiuqiong Huang; Siwa Msangi (International Water Management Institute, 2004)
IWMI-ADB Project